Efektivitas Program Earmarking Tax Atas Pajak Rokok Untuk Kesadaran Dalam Upaya Kesehatan Masyarakat di Provinsi DKI Jakarta - RD Kusyeni; Nur Sari; Ratih Kumala; Zainal Arifin Yurdani (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2021)
Effectiveness is needed to determine how far the targets have been achieved. Earmarking tax is a government policy in making efficient use of the budget in which the source of revenue and the spending program will be determined specifically as intended. DKI Jakarta is one of the provinces that implements earmarking tax on cigarette taxes. To find out the factors that influence the effectiveness of the earmarking program on cigarette taxes for awareness in public health efforts, the analysis uses Richard M Steer's theory of effectiveness which consists of four characteristics, namely organizational characteristics, environmental characteristics, worker characteristics and policy characteristics and management practices. Based on these four characteristics, the factors that support and influence the effectiveness of the earmarking tax program on cigarette taxes for awareness in public health efforts in DKI Jakarta Province are organizational characteristics. This is because the characteristics of the organization in its implementation are considered effective. One of the factors and efforts that have an impact on the effectiveness of this earmarking tax program, namely the overlapping authority between the central government and local governments, restrictions on the use of tax revenue-sharing funds and delays in depositing by the Ministry of Finance into regional general treasury accounts.